Downregulation of Mitochondrial TSPO Inhibits Mitophagy and Reduces Enucleation During Human Terminal Erythropoiesis - Moras, Martina (Int J Mol Sci, 2020)
Translocator protein (TSPO) and voltage dependent anion channels (VDAC) are two proteins forming a macromolecular complex in the outer mitochondrial membrane that is involved in pleiotropic functions. Specifically, these proteins were described to regulate the clearance of damaged mitochondria by selective mitophagy in non-erythroid immortalized cell lines. Although it is well established that erythroblast maturation in mammals depends on organelle clearance, less is known about mechanisms regulating this clearance throughout terminal erythropoiesis. Here, we studied the effect of TSPO1 downregulation and the action of Ro5-4864, a drug ligand known to bind to the TSPO/VDAC complex interface, in ex vivo human terminal erythropoiesis. We found that both treatments delay mitochondrial clearance, a process associated with reduced levels of the PINK1 protein, which is a key protein triggering canonical mitophagy. We also observed that TSPO1 downregulation blocks erythroblast maturation at the orthochromatic stage, decreases the enucleation rate, and increases cell death. Interestingly, TSPO1 downregulation does not modify reactive oxygen species (ROS) production nor intracellular adenosine triphosphate (ATP) levels. Ro5-4864 treatment recapitulates these phenotypes, strongly suggesting an active role of the TSPO/VDAC complex in selective mitophagy throughout human erythropoiesis. The present study links the function of the TSPO/VDAC complex to the PINK1/Parkin-dependent mitophagy induction during terminal erythropoiesis, leading to the proper completion of erythroid maturation.